2012
DOI: 10.1017/s0031182012001291
|View full text |Cite
|
Sign up to set email alerts
|

Morita-Baylis-Hillman adduct showsin vitroactivity againstLeishmania (Viannia) braziliensisassociated with a reduction in IL-6 and IL-10 but independent of nitric oxide

Abstract: Current treatments for different clinical forms of leishmaniasis are unsatisfactory, highly toxic and associated with increasing failure rates resulting from the emergence of resistant parasites. Leishmania (Viannia) braziliensis is the main aetiological agent of different clinical forms of American tegumentary leishmaniasis, including the mucosal form for which treatment has high failure rates. The aim of this work was to investigate the activity of the Morita-Baylis-Hillman adduct, methyl 2-{2-[hydroxy(2-nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Using an in vitro infection model, Hatzigeorgiou et al observed that IL-6 may reduce the macrophages killing activity against Leishmania [13]. The reduction in IL-6 may facilitate the activation of these macrophages and therefore, the containment of infection [14]. Similar results had been obtained by Kautz-Neu et al also for IL-1.…”
Section: Case Reportsupporting
confidence: 58%
“…Using an in vitro infection model, Hatzigeorgiou et al observed that IL-6 may reduce the macrophages killing activity against Leishmania [13]. The reduction in IL-6 may facilitate the activation of these macrophages and therefore, the containment of infection [14]. Similar results had been obtained by Kautz-Neu et al also for IL-1.…”
Section: Case Reportsupporting
confidence: 58%